An Evaluation of services for Children with Special Needs (CSN) : towards the formation of enhanced Academic Behavior Assistance Program (ABAP) - ESPALDON, ZIMRI MARIE (Archīum Ateneo, 2017)
This study evaluated the seven services of the Academic Behavior Assistance Program (ABAP), an assistance program for Children with Special Needs (CSN) at a traditional coeducational school in the National Capital Region. A total of 155 ABAP-Involved and Non-ABAP-Involved students, parents, and faculty were administered the researcher-designed Academic Behavior Assistance Program Services Survey (ABAPSS) tool that evaluated the Collaborative Team (CT), Individual Education Plan (IEP), Character Building Pull-Out Service (CB-POS), Monitoring Service (MS), Small Group Testing (SGT), Allowing Shadow Teacher (AST), Assisted Free Period (AFP), and ABAP Totality. The study found that respondents have varied perception of the ABAP services. Statistical data revealed significant differences in the perception of the CT, SGT, AFP, and ABAP Totality among respondents, and no significant differences in IEP, CB-POS, MS, and AST services. Based on the results of the ABAPSS and interviews, the researcher recommended the need to : (1) intensify the promotion of a well-structured ABAP; (2) consult frequently or once a trimester with CT members; (3) intensify teacher training through annual institutional seminars that include the orientation of the ABAP to new and old teachers; (4) intensify the implementation of ABAP services by incorporating the activities in the institutional academic calendar; (5) strengthen the involvement of other faculty members by appointing and training more ABAP teachers; (6) administer annually the ABAPSS to build the quality and effectiveness of the program; and (7) educate parents, teachers, and students about exceptional students and mental health during World Health Day in October.